Perancangan Sistem Informasi Absensi Pegawai di Kantor Pengacara - Onky Fatur Rahman; Ahmad Padil Rambe; Iman Adlin Sinaga (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
An employee attendance information system is an important tool used to manage and monitor employee attendance effectively. This research aims to design a computerized employee attendance information system for use in a lawyer's office. This system is designed to overcome various problems encountered in manual attendance recording methods, such as human error, inaccurate recording, and difficulties in accessing data in real-time. Designing this system involves analyzing user needs, designing a database, and implementing an intuitive user interface. The methods used include data collection through interviews and observations, analysis of ongoing systems, and design of new systems using tools such as flowcharts and data flow diagrams (DFD). The result of this research is a prototype of an attendance information system that can record employee attendance electronically, generate attendance reports automatically, and provide real-time data access to management. This system is also equipped with a notification feature for employees who are late or absent, as well as integration with the payroll system to make it easier to calculate salaries based on attendance. With this system, it is hoped that law offices can increase efficiency and accuracy in managing employee attendance, reduce administrative burdens, and provide more accurate data for decision making. It is hoped that the implementation of this employee attendance information system can become a model that can be applied in various other law firms, thereby increasing operational standards and professionalism in the legal industry..